THE INFLUENCE OF TAXATION ATTITUDE, AWARENESS AND KNOWLEDGE ON TAXPAYER COMPLIANCE IN PAYING LAND AND BUILDING TAXES IN CUBADAK VILLAGE MENTAWAI PARIAMAN TIMUR DISTRICT KOTA PARIAMAN - Primadyan, Maretha; Septiawati , Rika; Handayani, Deby (Universitas Sumatera Barat, 2023)
This study aims to examine the influence of taxpayer attitudes, taxpayer awareness, and taxation knowledge on taxpayer compliance in paying rural and urban land and building tax (PBB-P2). Researchers used quantitative descriptive methods with multiple regression analysis. The population in this study was taxpayers of Cubadak Mentawai Village, Pariaman City and obtained 84 data samples. The data obtained came from questionnaires. Researchers conduct classical assumption tests and hypothesis tests. The results of this study revealed that partially taxpayer attitudes did not significantly affect taxpayer compliance, taxpayer awareness had a significant effect on taxpayer compliance, while taxation knowledge had a significant effect on taxpayer compliance. However, based on the test results simultaneously reveal that taxpayer attitudes, taxpayer awareness, and taxation knowledge have a significant effect on taxpayer compliance.